ARHGAP11A maintains cortical progenitor identity through RHOA-ROCK signaling during human brain development - Hass, Yannick; Kniep, Julia; Hoffrichter, Anne; Marsoner, Fabio; Eşiyok, Nesil; Gasparotto, Matteo; Xing, Lei; Pio Loco detto Gava, Matteo; Artioli, Annasara; Guida, Catello; Meuth, Sven G.; Huttner, Wieland B.; et al. (Cell reports, 2025)
Mammalian brain development involves coordinated progenitor amplification, migration, and differentiation. Apical progenitors (APs) establish the ventricular zone (VZ) and are key determinants of brain size and complexity. Rho-family guanosine triphosphatases (Rho-GTPases) regulate cytoskeletal dynamics and AP behavior, but how specific Rho GTPase-activating proteins (Rho-GAPs) influence progenitor identity and VZ architecture remains unclear. Using human forebrain organoids, we investigate the function of the Rho GAP ARHGAP11A in human corticogenesis. CRISPR-Cas9-mediated ARHGAP11A knockout reveals its essential role in maintaining VZ integrity. Loss of ARHGAP11A impairs neuroepithelial organization and randomizes mitotic cleavage-plane orientation via the RHOA-ROCK-actin axis. This leads to premature AP delamination, AP depletion, and reduced cell density and glial numbers. Pharmacological inhibition of RHOA or ROCK rescues these defects, highlighting ARHGAP11A’s role in cytoskeletal remodeling to maintain cortical progenitors. Our findings establish ARHGAP11A as a critical regulator of AP identity and VZ integrity, with broad implications for human corticogenesis.
Gesehen am 29.01.2026